Nascer no século XXI em micro região paulista da Divisão Regional de Saúde (DRS XV) - Paes, Luciana Braz de Oliveira (2017)
Obstetric assistance is widely discussed in Brazil due to the excessive rates of caesarean surgeries (C-sections) and the disregard of ethical and legal norms, as well as of recommendations from national and international bodies regarding assistance in the pregnancy-puerperal cycle. OBJECTIVES: To investigate the sociodemographic and obstetric profile of women who delivered between 2006 and 2014, and C-sections performed in 2012. METHODS: This cross-sectional, descriptive, quantitative study was conducted in a micro-region of the 15th Regional Health Division of the State of São Paulo; it serves as a healthcare assistance reference for 19 municipalities. The study is linked to a larger project called “Studies on humanization in childbirth preparation and assistance: an emphasis on the role of the obstetric nurse” (Protocol CEP number 3921/2011). Data were retrieved in 2015 from the SINASC (Sistema de Informações de Nascidos Vivos, or Information System on Live Births). In order to identify associations between variables, the data were subjected to statistical analysis with a chi-square test, with a 5% significance level. RESULTS: Between 2006 and 2014, 2,447 women gave birth in the micro-region; the great majority of them were subjected to a C-section (57.4% in the public sector and 99.3% in the private sector); 73.5% were aged 20-34 years; 60% had a stable marital relationship; 62.6% had 8-11 years of schooling; 90.1% had attended seven or more prenatal consultations; 86.3% with gestational age between 37 and 41 weeks. There was a greatest number of C-sections in 2012 (64.6% in the public sector and 98.7% in the private sector); between 2006 and 2014, only 87 women seen in the private sector had natural childbirth. With regard to the profile of women subjected to C-sections in 2012, we found a statistical significance for C-section occurrence among women of older age and more education that had a partner and had attended a greater number of prenatal consultations. CONCLUSION: The data obtained in this study show that there is no scientific explanation for the steep increase in the number of cesarean sections (C-sections) in the nine years investigated. The sociodemographic characteristics influence C-section rates among women of a higher social class. Thus, actions and interventions to minimize cesarean sections without obstetric indication are needed. We suggest a greater number of obstetric nurses during labor, as well as a more active participation by pregnant women, so that medical services can fulfill national and international guidelines for the humanization of obstetric assistance.